Pemberdayaan Petani Desa Hutarimbaru melalui Pemanfaatan Limbah Perkebunan untuk Produksi Biopot sebagai Media Pembibitan: Indonesia - Harahap, Hamidah; Halimatuddahliana, Halimatuddahliana; Yustira, Ayuni (UII, 2026)
Hutarimbaru Village, South Panyabungan District, Mandailing Natal Regency, faces serious problems related to plantation waste management, particularly empty palm fruit bunches (EFB). This waste often piles up or is burned, causing environmental pollution. On the other hand, farmers still rely on expensive commercial seedling media, so that production costs absorb up to 35% of their income. This community service program aims to empower farmers by utilizing EFB and tea waste to make biodegradable pots as an alternative planting medium. Activities include socialization, training in manufacturing, procurement of shredders and hydraulic presses, as well as production assistance and quality testing. The results of the activities show an increase in farmers' skills in processing waste into useful products, a reduction in dependence on commercial media, and increased environmental awareness. The application has been proven to support better seedling growth while reducing waste. Thus, this program provides dual benefits, namely improving farmers' welfare and improving environmental quality.